Implication of oestrogen in the development of breast cancer: a brief narrative review - Nweze, Princess; U. Nwose, Ezekiel; O. Igumbor, Eunice (International Journal of Research in Medical Sciences, 2017)
The presence of hormones in milk and dairy foods was discussed decades ago but more concerns were with respect to finding hormones as biomarkers in milk for diseases and pregnancy diagnosis. Considerable amount of studies demonstrated that milk is essential for infants growing and immunity, while increasing body of evidence are indicating possible negative impact on human health including the role of some estrogens in the initiation and provoking of breast cancer. In this brief narrative, we reviewed recent data on oestrogens and breast cancer risk including comparative levels of hormones in cow milk, risk of breast cancer attributable to intake of different foods and lifestyle factors. Empirical findings indicate that consumption of cow milk is probably being over-emphasized as source of exogenous oestrogen, whereas control of alcohol as well as obesity and physical activity are under-emphasized in discourses on preventive protocols.